Characterization and chemical composition of epicuticular wax from banana leaves grown in Northern Thailand - Suporn Charumanee (2018)
© 2017, Prince of Songkla University. All rights reserved. This study aimed to investigate the physicochemical properties and chemical composition of epicuticular wax extracted from leaves of Kluai Namwa, a banana cultivar which is widely grown in Northern Thailand. Its genotype was identified by a botanist. The wax was extracted using solvent extraction. The fatty acid profiles and physicochemical properties of the wax namely melting point, congealing point, crystal structures and polymorphism, hardness, color, and solubility were examined and compared to those of beeswax, carnauba wax and paraffin wax. The results showed that the genotype of Kluai Namwa was Musa acuminata X M. balbisiana (ABB group) cv. Pisang Awak. The highest amount of wax extracted was 274 µg/cm2surface area. The fatty acid composition and the physicochemical properties of the wax were similar to those of carnauba wax. It could be suggested that the banana wax could be used as a replacement for carnauba wax in various utilizing areas.